1999
DOI: 10.1002/(sici)1521-3765(19990503)5:5<1512::aid-chem1512>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Disaccharides, Containing Sulfur in the Ring of the Reducing Monosaccharide Unit, Through a Nonglycosylating Chemical Strategy

Abstract: A novel ring‐opening–recyclisation approach of the nonreducing sugar residue is reported for the formation of thio sugars from vicinal diols of natural disaccharides (lactose, maltose and cellobiose; see scheme), via cyclic sulfates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Keeping the retrosynthetic strategy in mind, we started the synthesis of 22 from the 1,6-anhydro disaccharide 17 , which was prepared from d -(+)-cellobiose (Scheme ). Compound 17 was prepared by simple acetonation of cellobiose under modified Isac-García conditions . After testing several different conditions to obtain the tri- O -isopropylidene dimethyl acetal, we observed that addition of dry SiO 2 to the reaction mixture significantly increases the yield.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Keeping the retrosynthetic strategy in mind, we started the synthesis of 22 from the 1,6-anhydro disaccharide 17 , which was prepared from d -(+)-cellobiose (Scheme ). Compound 17 was prepared by simple acetonation of cellobiose under modified Isac-García conditions . After testing several different conditions to obtain the tri- O -isopropylidene dimethyl acetal, we observed that addition of dry SiO 2 to the reaction mixture significantly increases the yield.…”
Section: Results and Discussionmentioning
confidence: 99%